The quality of health care for adults with developmental disabilities - Lewis, Mary Ann; Lewis, Charles E; Leake, Barbara; King, Bryan H; Lindemann, Robert (Public health reports (1974), 2002)
The purpose of this study was to determine the health status of adults with developmental disabilities residing in community settings and the quality of the preventive, medical, dental, and psychiatric services they receive.OBJECTIVEThe purpose of this study was to determine the health status of adults with developmental disabilities residing in community settings and the quality of the preventive, medical, dental, and psychiatric services they receive.Data were collected on a sample of 353 adults residing in Los Angeles, California, in 1997. Historical data were obtained from study subjects or caregivers, physical and dental examinations were performed, blood was drawn for analysis, and a psychiatrist reviewed medical records for reports of psychiatric diagnoses and consultations.METHODSData were collected on a sample of 353 adults residing in Los Angeles, California, in 1997. Historical data were obtained from study subjects or caregivers, physical and dental examinations were performed, blood was drawn for analysis, and a psychiatrist reviewed medical records for reports of psychiatric diagnoses and consultations.Health markers, such as rates of obesity, and laboratory test results of routine screening panels including blood cell counts, hemoglobin, and hematocrits; blood concentrations of liver enzymes and other enzymes, cholesterol, and tryglycerides; and urinalyses were within normal limits for an adult population. However, preventive services were notably lacking, especially for individuals living at home. Fewer than half of the study subjects had received influenza vaccine; only a third of those living alone or with family or friends had received this vaccination. Chart audits revealed that about a third received psychotropic medications, but only 24% of these individuals had psychiatric consultations noted in their record. Further, 36% of this medicated group received psychotropic drugs without any identifiable diagnosis, and simultaneous receipt of two or more antipsychotics was not uncommon.RESULTSHealth markers, such as rates of obesity, and laboratory test results of routine screening panels including blood cell counts, hemoglobin, and hematocrits; blood concentrations of liver enzymes and other enzymes, cholesterol, and tryglycerides; and urinalyses were within normal limits for an adult population. However, preventive services were notably lacking, especially for individuals living at home. Fewer than half of the study subjects had received influenza vaccine; only a third of those living alone or with family or friends had received this vaccination. Chart audits revealed that about a third received psychotropic medications, but only 24% of these individuals had psychiatric consultations noted in their record. Further, 36% of this medicated group received psychotropic drugs without any identifiable diagnosis, and simultaneous receipt of two or more antipsychotics was not uncommon.Given that the U.S. health care system fails to ensure the provision of preventive services for all people, including the developmentally disabled, a systematic overhaul is necessary to establish an effective quality assurance program that will provide preventive medical, dental, and psychiatric services for people with developmental disabilities.CONCLUSIONSGiven that the U.S. health care system fails to ensure the provision of preventive services for all people, including the developmentally disabled, a systematic overhaul is necessary to establish an effective quality assurance program that will provide preventive medical, dental, and psychiatric services for people with developmental disabilities.